Study by GC-MS method of Thymus x citriodorus (Pers.) Schreb. var. "Silver Queen" extracts component composition - Ya. M. Steshenko; O. V. Mazulin (Zaporozhye State Medical University, 2022)
The Thyme L. genus is quite common in Ukraine, herbal extracts are part of many effective herbal medicinal products that are widely used in modern phytocosmetology. Today, genus Thymus x citriodorus (Pers.) Schreb. var. "Silver Queen" is poorly studied but promising in terms of sufficient raw material base and BAS. Therefore, the GC-MS method of designating the component of the extract from herb splint is relevant. The aim of the work is to determine by the GC-MS method of the component alcohol extracts (1:10) compositions of Thymus x citriodorus (Pers.) Schreb. var. "Silver Queen" herbs from Ukrainian flora. Materials and methods. For the experimental studies, we used alcoholic extracts of Thymus х citriodorus (Pers.) Schreb. var. "Silver Queen" from herbs (1:10) harvested from Ukrainian flora. The component composition of extracts was analyzed using an Agilent 7890B gas chromatography with 5977B a mass - spectrometric detector. Results. By the GC-MS method were revealed up to 63 compounds. Two compounds were not identified. It is important to note, that seven biologically active compounds were revealed in a concentration over 5 %: oleic acid (10.35 ± 1.42 %), caryophyllene oxide (9.62 ± 0.97 %), matricarin (7.59 ± 0.86 %), trans-citral (6.35 ± 0.75 %), β-bisabolene (6.15 ± 0.75 %), thymol (5.46 ± 0.70 %). Conclusions. Taking into account by GC-MS method, it can be concluded that the studied species is relevant for further phytochemical study.